The Maximum Power Point Tracking of Stand-alone Photovoltaic System Using Fuzzy Logic - Kongsawat, Korakod; Soppaperm, Thappanom (Srinakharinwirot University Engineering Journal, 2021)
This paper presents the maximum power point tracking of stand-alone photovoltaic system using fuzzy logic method. That will be applied in buck converter circuit for developing system to faster convergence Therefore, computer simulations are simulated in order to compare performance characteristics of perturbation and observation methods found that fuzzy logic method faster convergence than the perturbation and observation method state during the system initialization and the irradiance condition changes, so the system can effectively the maximum power of the photovoltaic system and therefore creating equipment that was designed. The results reviewed that fuzzy logic method could track rapid maximum power and accurate than with perturbation and observation method.